2020
DOI: 10.1021/acs.joc.0c01692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a 3,4-Dihydro-1,3-oxazin-2-ones Skeleton via an Intermolecular [4 + 2] Process of N-Acyliminium Ions with Ynamides/Terminal Alkynes

Abstract: An approach to access functionalized 3,4-dihydro-1,3-oxazin-2-ones has been developed by reacting semicyclic N,O-acetals 5 and 6 with ynamides 7 or terminal alkynes 8 in a one-pot fashion. The reaction went through a formal [4 + 2] cycloaddition process to generate a number of functionalized 3,4-dihydro-1,3-oxazin-2-ones 9a–9ak and 10a–10bc in yields of 34–97%. In addition, the utility of this transformation was demonstrated by the synthesis of (±)-sedamine 13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…3. 19 First, N -acyliminium ion Int-1 was generated from N , O -acetal 1a in the presence of AgNTf 2 . Then the terminal alkyne 2a was regioselectively reacted from the less steric side of the diene type Int-2 to obtain a six-membered intermediate Int-3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3. 19 First, N -acyliminium ion Int-1 was generated from N , O -acetal 1a in the presence of AgNTf 2 . Then the terminal alkyne 2a was regioselectively reacted from the less steric side of the diene type Int-2 to obtain a six-membered intermediate Int-3 .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple Lewis acids, including BF 3 ·OEt 2 , SIPrAuCl/AgSbF 6 16 and Cu(OTf) 2 , 17 were applied to catalyze the nucleophilic addition–cyclization of cyclic N , O -acetals with ynamides. Recently, we reported that strong Lewis acids, including BF 3 ·OEt 2 18 and TMSOTf, 19 could mediate the intermolecular [4 + 2] cycloaddition of cyclic N , O -acetals or semicyclic N , O -acetals with terminal alkynes. Based on our previous experience in this field, weak Lewis acids could catalyze the reaction with highly reactive benzyl activated N , O -acetals, 20 while strong Lewis acids were usually required for the reaction with less reactive semicyclic N , O -acetals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a metal‐free, TMSOTf‐promoted reaction of various semi‐cyclic N, O‐acetals 96 with different alkynes 97 was studied by Wei and co‐workers for the rapid assembly of differently substituted oxazin‐2‐ones 98 in good to excellent yield (Scheme 32). [73] The developed method portrayed excellent scope, particularly with respect to alkynes ranging from aryl/alkyl alkynes to ynamides. The proposed mechanism involved acid‐catalysed generation of iminium ion Int ‐ BC , which upon carboalkoxylation led to the formation of Int ‐ BD .…”
Section: Carboalkoxylationmentioning
confidence: 99%
“…And the author thinks that the mechanism of the reaction includes a Diels–Alder step (Figure b) . As a continuation of our interest in developing a methodology of rapid access to diverse scaffolds for natural products, herein we present a successive Michael addition and subsequent decarboxylative–Mannich process, representing a combination strategy for a one-pot organocatalytic reaction from α,β-unsaturated ketones and amino acids (Figure c).…”
Section: Introductionmentioning
confidence: 99%